Carbon fiber reinforced cement-based composite material as well as preparation method and application thereof

By preparing water-soluble carbon fiber pellets and dispersing them evenly in cement, the problem of decreasing flexural strength and bending deflection of cement composites under high carbon fiber content is solved, and the high performance of the material and the simplification of the process is achieved.

CN119874238APending Publication Date: 2025-04-25SUN YAT SEN UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510103289.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-22
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

When the carbon fiber content is high (carbon fiber accounts for more than 1.5% of the cement mass), the flexural strength and bending deflection of carbon fiber reinforced cement composites will decrease, resulting in a decrease in the safety and reliability of the material.

Method used

Cut carbon fiber is used to make water-soluble carbon fiber pellets of a certain average particle size. By uniformly mixing, drying and pelleting with the water-soluble polymer solution, a two-stage dispersion system is formed to ensure that the carbon fiber is evenly dispersed in cement.

Benefits of technology

It is achieved that the flexural strength and bending deflection of cement composite materials are maintained at a high level under high carbon fiber content, which improves the safety and reliability of the material, and simplifies the process and is suitable for large-scale production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119874238A_ABST
    Figure CN119874238A_ABST
Patent Text Reader

Abstract

The invention relates to a carbon fiber reinforced cement-based composite material as well as a preparation method and application thereof. The preparation method of the carbon fiber granules comprises the following steps: uniformly mixing short carbon fibers and a water-soluble polymer solution, drying, and granulating to obtain the carbon fiber granules, the mass ratio of the short carbon fibers to the water-soluble polymer of the water-soluble polymer aqueous solution is 7: (1-7); and the average particle size of the carbon fiber granules is 5-20 mm. The short carbon fibers are adopted to prepare the water-soluble carbon fiber granules with a certain average particle size, the water-soluble carbon fiber granules are used for preparing the carbon fiber reinforced cement-based composite material, and the high-content short carbon fibers can be doped into cement to form a two-stage dispersion system, so that the breaking strength and the bending deflection of the cement composite material are kept at a high level at the same time.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of building materials, and more specifically, to a carbon fiber reinforced cement-based composite material and a preparation method and application thereof. Background Art

[0002] Cement concrete is a brittle material. Adding short fibers such as chopped carbon fibers to cement concrete for toughening is a common modification method. At a lower carbon fiber content, the flexural strength and bending deflection of cement composites can be improved. However, when the content of carbon fibers mixed into cement concrete reaches a certain level (carbon fibers account for more than 1.5% of the mass of cement), further increasing the content of carbon fibers will cause carbon fibers to agglomerate in cement composites due to their large specific surface area and become entangled with each other. Cement concrete is difficult to infiltrate the interior of the carbon fiber clusters, leaving defects and gaps in the formed cement composites. At this time, the flexural strength and bending deflection of the cement composite will decrease significantly. In particular, the bending deflection decreases and the toughness deteriorates. When the cement composite bears a load, the load distribution area is smaller, making it easier to be damaged, and the safety and reliability decrease.

[0003] A Chinese patent discloses a method for drying and dispersing carbon fiber in cement powder. The method directly mixes short-cut carbon fiber in a monofilament state with cement powder, and then adds water for curing to prepare a carbon fiber reinforced cement-based composite material, thereby achieving uniform dispersion of carbon fiber in cement powder. However, the patent only explores the dispersion of carbon fiber when the mass of silicate cement is less than 0.8%, and does not explore the dispersion of higher content carbon fiber in silicate cement.

[0004] The literature (DOI: 10.1016 / j.jclepro.2019.01.256) uses embedded carbon fiber mesh combined with cement-based concrete to improve the mechanical properties of cement composites. However, this preparation method is complicated and not suitable for large-scale production. There are technical difficulties in industrial transformation.

[0005] Therefore, it is necessary to solve the problem that the flexural strength and bending deflection of carbon fiber reinforced cement composite materials decrease when the carbon fiber content is high (the carbon fiber accounts for more than 1.5% of the cement mass). Summary of the invention

[0006] The primary purpose of the present invention is to overcome the problem that the flexural strength and bending deflection of the above-mentioned existing carbon fiber reinforced cement composite materials decrease when the carbon fiber content is high (the carbon fiber accounts for more than 1.5% of the cement mass), and to provide a method for preparing carbon fiber granules. The present invention uses short-cut carbon fibers to make water-soluble carbon fiber granules with a certain average particle size, which are used to prepare carbon fiber reinforced cement-based composite materials. A high content of short-cut carbon fibers can be added to cement, so that the flexural strength and bending deflection of the cement composite materials are maintained at a high level at the same time.

[0007] A further object of the present invention is to provide a carbon fiber pellet.

[0008] Another object of the present invention is to provide the use of the above carbon fiber granules in the preparation of carbon fiber reinforced cement-based composite materials.

[0009] Another object of the present invention is to provide a carbon fiber reinforced cement-based composite material.

[0010] Another object of the present invention is to provide a method for preparing the above-mentioned carbon fiber reinforced cement-based composite material.

[0011] The above-mentioned object of the present invention is achieved by the following technical solutions:

[0012] A method for preparing carbon fiber pellets comprises the following steps: uniformly mixing chopped carbon fibers with a water-soluble polymer solution, drying, and pelletizing to obtain the carbon fiber pellets;

[0013] The mass ratio of the chopped carbon fiber to the water-soluble polymer in the water-soluble polymer aqueous solution is 7:(1-7); and the average particle size of the carbon fiber granules is 5-20 mm.

[0014] In previous studies, when the carbon fiber content reaches more than 1.5% of the cement mass, the carbon fibers tend to agglomerate in the cement matrix due to their large specific surface area and become entangled with each other. The cement matrix has difficulty infiltrating into the interior of the carbon fiber clusters, leaving defects and voids in the composite material sample, causing the flexural strength and bending deflection of the cement composite material to decrease with the increase in the carbon fiber content.

[0015] The present invention uses short-cut carbon fibers to make water-soluble carbon fiber pellets with a certain average particle size, which are used to prepare carbon fiber reinforced cement-based composite materials. A high content of short-cut carbon fibers can be added to cement to form a two-stage dispersion system, so that the flexural strength and bending deflection of the cement composite material are maintained at a high level at the same time. The principle is: on the one hand, the average particle size of the carbon fiber pellets is regulated within a certain range, and the specific surface area of ​​the carbon fiber pellets is small, so that the short-cut carbon fibers can be mixed into cement without agglomeration (carbon fiber primary dispersion system); on the other hand, when the cement is solidified, the short-cut carbon fibers are dissolved in situ and the pellets are dissolved, so that the short-cut carbon fibers are mixed with cement in situ to form a reinforcement zone (carbon fiber secondary dispersion system). The improvement of the flexural strength and bending deflection of the reinforced area is mainly reflected in: 1) The reinforced area is formed by the self-dissociation of carbon fiber particles, which facilitates the infiltration of cement into the reinforced area and mixing with the chopped carbon fibers, reducing the internal porosity of the composite material, thereby improving the flexural strength and bending deflection; 2) The diffusion of the chopped carbon fibers in the outer layer of the reinforced area not only plays a role in stress transfer and bridging toughening, but also forms a transition zone between cement and the reinforced area, further expanding the scope of the reinforced area, thereby improving the flexural strength and bending deflection of the composite material; 3) When the cement composite material is subjected to compression and flexure, when the crack extends to the reinforced area, the crack deflects to form a larger surface, which requires more energy to consume, thereby improving the energy absorption rate of the composite material, thereby improving the flexural strength of the composite material.

[0016] The inventors of the present invention have discovered through research that if the average particle size of the carbon fiber pellets is too large, on the one hand, the amount of carbon fiber pellets incorporated into the cement matrix will be reduced, and the pellets will be difficult to distribute evenly in the carbon fiber reinforced cement-based composite material; on the other hand, its surface area is too small, making it difficult for the cement matrix to infiltrate the interior of the pellets, and the internal defects of the sample will increase and increase. These two effects lead to low bending deflection of the composite material; if the average particle size of the carbon fiber pellets is too small, the uniformity of the pellets will be difficult to control, resulting in the inability to maintain the bending deflection of the composite material at a high level.

[0017] The inventors of the present invention also found through research that if the water-soluble polymer accounts for too large a proportion of the mass of the carbon fiber pellets, the redundant water-soluble polymer becomes an impurity, which reduces the bending deflection of the prepared carbon fiber reinforced cement-based composite material; if the water-soluble polymer accounts for too small a proportion of the mass of the carbon fiber pellets, the prepared carbon fiber pellets are loose and cannot form pellets.

[0018] In the present invention, the mass ratio of the chopped carbon fibers to the water-soluble polymer in the water-soluble polymer aqueous solution can be 7:1, 7:1.5, 7:2, 7:2.5, 7:3, 7:3.5, 7:4, 7:4.5, 7:5, 7:5.5, 7:6, 7:6.5 or 7:7.

[0019] Preferably, the mass ratio of the chopped carbon fibers to the water-soluble polymer in the water-soluble polymer aqueous solution is 7:(2-6).

[0020] More preferably, the mass ratio of the chopped carbon fibers to the water-soluble polymer in the water-soluble polymer aqueous solution is 7:(3-5.5).

[0021] Preferably, the average particle size of the carbon fiber granules is 5 to 12 mm.

[0022] Preferably, the water-soluble polymer in the water-soluble polymer solution is at least one of polyvinyl alcohol, polyacrylamide, water-soluble starch or water-soluble cellulose.

[0023] More preferably, the water-soluble polymer is polyvinyl alcohol.

[0024] Preferably, the average degree of polymerization of the water-soluble polymer is 1500-1900.

[0025] Preferably, the concentration of the water-soluble polymer in the water-soluble polymer solution is 5 to 20 wt %.

[0026] Preferably, the average length of the chopped carbon fibers is 1 to 6 mm.

[0027] Preferably, the average diameter of the chopped carbon fibers is 4.5-10 μm.

[0028] Preferably, the average aspect ratio of the chopped carbon fibers is 140-860.

[0029] Preferably, the chopped carbon fiber is obtained by chopping one or more of continuous carbon fiber, long carbon fiber or recycled carbon fiber into short pieces.

[0030] The present invention also protects a carbon fiber granular material, which is prepared by the above preparation method.

[0031] The use of the above carbon fiber granules in the preparation of carbon fiber reinforced cement-based composite materials is also within the protection scope of the present invention.

[0032] The present invention also protects a carbon fiber reinforced cement-based composite material, comprising the following components in parts by mass: 2 to 5 parts of the above carbon fiber granules and 100 parts of cement.

[0033] Preferably, the chopped carbon fibers in the carbon fiber pellets account for more than 1.5% of the mass of the cement.

[0034] More preferably, the chopped carbon fibers in the carbon fiber pellets account for 1.5-5% of the mass of the cement.

[0035] Further preferably, the chopped carbon fibers in the carbon fiber granules account for 1.5-3.2% of the mass of the cement. Within this range, the bending deflection is kept at a high level, and the flexural strength of the carbon fiber reinforced cement-based composite material is higher.

[0036] The present invention also protects a method for preparing a carbon fiber reinforced cement-based composite material, comprising the following steps: weighing each component and mixing it with water, and then curing to obtain the carbon fiber reinforced cement-based composite material.

[0037] Preferably, the mixing method is mechanical stirring.

[0038] Compared with the prior art, the present invention has the following beneficial effects:

[0039] The present invention uses short-cut carbon fibers to make water-soluble carbon fiber pellets with a certain average particle size, which are used to prepare carbon fiber reinforced cement-based composite materials. A high content of short-cut carbon fibers can be added to cement to form a two-stage dispersion system, so that the flexural strength and bending deflection of the cement composite material are maintained at a high level at the same time. In addition, the preparation method of the present invention is simple in process, suitable for large-scale production, and has market competitiveness. BRIEF DESCRIPTION OF THE DRAWINGS

[0040] Figure 1 This is the SEM image of the carbon fiber pellets of Example 1.

[0041] Figure 2 This is the SEM image of the carbon fiber reinforced cement-based composite material of Example 4.

[0042] Figure 3 This is the SEM image of the cement-based composite material of Comparative Example 2.

[0043] Figure 4 This is the SEM image of the cement-based composite material of Comparative Example 4. DETAILED DESCRIPTION

[0044] In order to more clearly and completely describe the technical solution of the present invention, the present invention is further described in detail through specific embodiments below. It should be understood that the specific embodiments described herein are only used to explain the present invention, and are not used to limit the present invention. Various changes can be made within the scope of the rights of the present invention.

[0045] The raw materials used in the present invention are described as follows:

[0046] Chopped carbon fiber: model T300-12K, average diameter 7μm, average length 3mm;

[0047] Cement: PO 42.5 Portland cement;

[0048] Polyvinyl alcohol: Type 1788, degree of polymerization is 1700.

[0049] Example 1

[0050] This embodiment provides a method for preparing carbon fiber pellets, comprising the following steps: mixing water and polyvinyl alcohol at a mass ratio of 9:1 at room temperature, stirring for 30 minutes, and obtaining a polyvinyl alcohol solution. Then, evenly mixing the chopped carbon fiber and the polyvinyl alcohol solution, pouring them into a mold, and drying them in a drying oven for 72 hours to obtain a carbon fiber block, and using a cutting machine to cut the carbon fiber block into pellets to obtain carbon fiber pellets. Among them, the mass ratio of the chopped carbon fiber to the polyvinyl alcohol in the polyvinyl alcohol solution is 7:3; the average particle size of the carbon fiber pellets is 8 mm.

[0051] Example 2

[0052] This embodiment provides a method for preparing carbon fiber pellets. The difference from Embodiment 1 is that the mass ratio of the chopped carbon fibers to the polyvinyl alcohol in the polyvinyl alcohol solution is 7:5.25.

[0053] Example 3

[0054] This embodiment provides a method for preparing carbon fiber pellets. Different from Embodiment 1, the average particle size of the carbon fiber pellets is 20 mm.

[0055] Example 4

[0056] This embodiment provides a carbon fiber reinforced cement-based composite material, comprising the following components in parts by weight: 2.165 parts of carbon fiber granules prepared in Example 1 and 100 parts of cement. The amount of chopped carbon fiber added is equivalent to 1.52wt% of the cement mass.

[0057] The preparation method of the carbon fiber reinforced cement-based composite material in this embodiment includes the following steps: after cement and water are mixed evenly (the amount of water used: 50 parts), the carbon fiber pellets prepared in Example 1 are added, and after stirring evenly, they are injected into a mold. After 1 day, after the sample is formed, it is taken out of the mold and placed in a constant temperature and humidity curing box for curing for 6 days to obtain a carbon fiber reinforced cement-based composite material.

[0058] Example 5

[0059] This embodiment provides a carbon fiber reinforced cement-based composite material, which is different from the embodiment 4 in that the amount of carbon fiber granules used is 4.373 parts. The amount of chopped carbon fiber added is equivalent to 3.06wt% of the mass of cement.

[0060] The preparation method of the carbon fiber reinforced cement-based composite material in this embodiment is the same as that in Example 4.

[0061] Example 6

[0062] This embodiment provides a carbon fiber reinforced cement-based composite material, which is different from the embodiment 4 in that the amount of carbon fiber granules used is 6.627 parts, and the amount of chopped carbon fiber added is equivalent to 4.64wt% of the mass of cement.

[0063] The preparation method of the carbon fiber reinforced cement-based composite material in this embodiment is the same as that in Example 4.

[0064] Example 7

[0065] This embodiment provides a carbon fiber reinforced cement-based composite material. The difference from Embodiment 4 is that the carbon fiber pellets prepared in Embodiment 1 are replaced by the carbon fiber pellets prepared in Embodiment 2.

[0066] The preparation method of the carbon fiber reinforced cement-based composite material in this embodiment is the same as that in Example 4.

[0067] Example 8

[0068] This embodiment provides a carbon fiber reinforced cement-based composite material. The difference from Embodiment 4 is that the carbon fiber pellets prepared in Embodiment 1 are replaced by the carbon fiber pellets prepared in Embodiment 3.

[0069] The preparation method of the carbon fiber reinforced cement-based composite material in this embodiment is the same as that in Example 4.

[0070] Comparative Example 1

[0071] This comparative example provides a pure cement material, which is different from Example 4 in that no carbon fiber granules are added.

[0072] The preparation method of the pure cement material of this comparative example comprises the following steps: cement and water (cement to water mass ratio is 100:50) are mixed evenly and then injected into a mold; after one day, the sample is taken out of the mold after being formed, and placed in a constant temperature and humidity curing box for curing for 6 days to obtain the pure cement material.

[0073] Comparative Example 2

[0074] This comparative example provides a cement-based composite material, which is different from Example 4 in that 2.165 parts of carbon fiber pellets are replaced with 1.515 parts of chopped carbon fibers, which is equivalent to not making the chopped carbon fibers into fiber pellets but directly mixing them into cement.

[0075] The preparation method of the cement-based composite material of this comparative example comprises the following steps: after cement and water (water dosage: 50 parts) are mixed evenly, short-cut carbon fibers are added, and after stirring evenly, the mixture is injected into a mold. After one day, after the sample is formed, the mold is taken out, and the sample is placed in a constant temperature and humidity curing box for curing for 6 days to obtain a cement-based composite material.

[0076] Comparative Example 3

[0077] This comparative example provides a cement-based composite material, which is different from comparative example 2 in that the amount of chopped carbon fibers used is 3.061 parts.

[0078] The preparation method of the cement-based composite material in this comparative example is the same as that of comparative example 2.

[0079] Comparative Example 4

[0080] This comparative example provides a cement-based composite material, which is different from comparative example 2 in that the amount of chopped carbon fibers used is 4.639 parts.

[0081] The preparation method of the cement-based composite material in this comparative example is the same as that of comparative example 2.

[0082] Sample characterization and performance testing

[0083] 1. Sample Characterization

[0084] The carbon fiber aggregates of Example 1, the carbon fiber reinforced cement-based composite material of Example 4, and the cement-based composite materials of Comparative Examples 2 and 4 were subjected to SEM testing. The results are as follows: Figures 1 to 4 shown. Figure 1 is a SEM image of the carbon fiber pellets of Example 1; Figure 2 This is a SEM image of the carbon fiber reinforced cement-based composite material of Example 4; Figure 3 is a SEM image of the cement-based composite material of Comparative Example 2; Figure 4 This is the SEM image of the cement-based composite material of Comparative Example 4.

[0085] from Figure 1 It can be seen that the chopped carbon fibers are evenly distributed in the carbon fiber pellets. Figure 2 It can be seen that the chopped carbon fibers in the carbon fiber reinforced cement-based composite material of Example 4 are mixed with cement in situ, the cement matrix infiltrates into the chopped carbon fiber clusters, and the chopped carbon fibers are evenly dispersed in the cement matrix. Most of the chopped carbon fibers overlap each other, and there is no agglomeration of the chopped carbon fibers. The SEM test results of Examples 5 to 8 are similar to those of Example 4. The above shows that the carbon fiber granules prepared by the present invention can be effectively dispersed in the carbon fiber reinforced cement-based composite material, avoiding agglomeration, which is beneficial to improving the flexural strength and bending deflection.

[0086] from Figure 3 and Figure 4 It can be seen that the chopped carbon fibers agglomerate in the cement-based composite materials of Comparative Examples 2 and 4. The chopped carbon fibers are entangled with each other, and it is difficult for the cement matrix to penetrate into the chopped carbon fiber clusters.

[0087] 2. Performance Testing

[0088] The carbon fiber reinforced cement-based composite materials of Examples 4 to 8, the pure cement material of Comparative Example 1, and the cement-based composite materials of Comparative Examples 2 to 4 were tested for flexural strength and bending deflection. The test standard was GB / T 17671-2021 "Test method for strength of cement mortar (ISO method)", and the test results are shown in Table 1.

[0089] Table 1 Test results of flexural strength and bending deflection

[0090] Flexural strength(MPa) Bending deflection(mm) Example 4 11.39 0.768 Example 5 10.91 0.760 Example 6 8.43 0.762 Comparative Example 1 5.51 0.282 Comparative Example 2 9.22 0.562 Comparative Example 3 8.54 0.542 Comparative Example 4 8.39 0.540

[0091] As can be seen from Table 1, the bending deflection of the carbon fiber reinforced cement-based composite materials of Examples 4 to 6 is above 0.760 mm, which shows that the carbon fiber granules of the present invention are used to prepare carbon fiber reinforced cement-based composite materials. When the chopped carbon fiber content reaches more than 1.5% of the cement mass, the bending deflection of the cement composite material is high, and as the chopped carbon fiber content gradually increases, the bending deflection of the cement composite material does not decrease, but remains at a high level. In addition, the flexural strength of the carbon fiber reinforced cement-based composite materials of Examples 4 to 6 is above 8.43 MPa, which shows that the carbon fiber granules of the present invention are used to prepare carbon fiber reinforced cement-based composite materials and improve the flexural strength of the composite material. The experimental results of Examples 7 to 8 are similar to those of Example 4.

[0092] Comparative Example 1 is a pure cement sample without adding carbon fiber, and its bending deflection and flexural strength are relatively low.

[0093] The carbon fiber content of Comparative Examples 2 to 4 reaches more than 1.5% of the cement mass, and the bending deflection of the cement-based composite material is not as good as that of Examples 4 to 6. As the content of chopped carbon fiber gradually increases, the bending deflection of the cement-based composite material gradually decreases and cannot be maintained at a high level.

[0094] In addition, the flexural strength of the cement-based composite materials of Comparative Examples 2, 3 and 4 is lower than that of Examples 4, 5 and 6, respectively.

[0095] Obviously, the above embodiments of the present invention are merely examples for clearly illustrating the present invention, and are not intended to limit the embodiments of the present invention. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the embodiments here. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the claims of the present invention.

Claims

1. A method for preparing carbon fiber pellets, characterized in that: The following steps are involved: The chopped carbon fibers are uniformly mixed with the water-soluble polymer aqueous solution, dried, and pelletized to obtain the carbon fiber pellets; The mass ratio of the chopped carbon fiber to the water-soluble polymer in the water-soluble polymer aqueous solution is 7:(1-7); and the average particle size of the carbon fiber granules is 5-20 mm.

2. The preparation method according to claim 1, characterized in that: The water-soluble polymer in the water-soluble polymer solution is at least one of polyvinyl alcohol, polyacrylamide, water-soluble starch or water-soluble cellulose.

3. The preparation method according to claim 1, characterized in that: The concentration of the water-soluble polymer in the water-soluble polymer solution is 5 to 20 wt %.

4. The preparation method according to claim 1, characterized in that: The average length of the chopped carbon fibers is 1 to 6 mm.

5. The preparation method according to claim 1, characterized in that: The average aspect ratio of the chopped carbon fibers is 140-860.

6. A carbon fiber pellet, characterized in that: It is prepared by the preparation method according to any one of claims 1 to 5.

7. Use of the carbon fiber granules according to claim 6 in the preparation of carbon fiber reinforced cement-based composite materials.

8. A carbon fiber reinforced cement-based composite material, characterized in that: The invention comprises the following components in parts by mass: 2 to 5 parts of the carbon fiber granules as claimed in claim 6 and 100 parts of cement.

9. The carbon fiber reinforced cement-based composite material according to claim 8, characterized in that: The chopped carbon fibers in the carbon fiber granules account for more than 1.5% of the mass of the cement.

10. A method for preparing a carbon fiber reinforced cement-based composite material, characterized in that: The method comprises the following steps: weighing each component and mixing with water, stirring evenly, and curing to obtain the carbon fiber reinforced cement-based composite material.